Morphometric Study of the Asterion in Adult Dry Human Skulls of Nigerian Origin - Godswill, Okoro Ogheneyebrorue; O, Oyovwi Mega; Udi, Onoriode Andrew; Onoriode, Igben Vincent-Junior; Owhefere, Owhefere Great (International Journal of Human and Health Sciences (IJHHS), 2023)
Background: The asterion, where the temporal, occipital, and parietal bones converge on the posterolateral aspect of the skull, is a critical reference point for surgeons when approaching the structures of the posterior fossa. Objective: This cross-sectional study wasconducted to assess the linear distances of asterion from various bony landmarks and their proximity to the transverse sinus, as well as to categorizeasterion types based on the presence or absence of suture bone. Methods: A total of 20 skulls were examined and the type of asterion was determined as type I and type II depending on the presence or absence of sutural bone. The distance from the centre of asterion to tip of the mastoid process and supramastoid process weremeasured. Data were analyzed with Student t-test. Results: Our data revealed that type II (absence of sutural bones) was commoner than type I (presence of sutural bones)asterion. The asterion was 55.72±2.60 mm from tip of the mastoid process on the right side and 51.07±1.43 mm on the left, p value being statistically significant (P=0.001). The distance of asterionfrom supramastoid crest was 47.16±1.47 mm on the right and 43.80±1.97 mm on the left. P value 0.002 was statistically significant. Conclusion: The asterion is usually located either at or below the level of the transverse sinus, according to the data collected. Neurosurgeons can adopt this knowledge to lessen the danger of posterior fossa surgery. International Journal of Human and Health Sciences Vol. 07 No. 01 Jan’22 Page: 31-34